40Ar-39Ar analyses of Yamato-75097 (L6) chondrite from Antarctica - Kaneoka, Ichiro; Takaoka, Nobuo; Yanai, Keizo (National Institute of Polar Research, 1988)
P(論文) ^<40>Ar-^<39>Ar analyses were performed on the host phase of an H-clast bearing chondrite Yamato-75097 (L6). The result indicates a typical U-shaped age spectrum, suggesting that the serious degassing event occurred at about 490Ma or slightly younger age for this meteorite. Since the meteorite shows a sign of shock, this event might have been a collisional event. It is estimated that more than 99% of radiogenic ^<40>Ar was degassed during this event. For this degassing, it requires prolonged time of at least a few hours even at 1200℃, and a longer time is required if the ambient temperature is lower and the diffusion mainly controls the degassing process. departmental bulletin paper